Food and housing security at a US Hispanic-Serving Institution: An examination before and during the COVID-19 pandemic - Amy Wagler; Gregory S. Schober; Silvia M. Chavez-Baray; Silvia M. Chavez-Baray; Jessica Ayala; Paul R. Dessauer; Eva M. Moya (Frontiers Media S.A., 2022)
University students occupy a socially marginal position and therefore are often underserved by academic and service institutions. This article analyzes food and housing security among students at The University of Texas at El Paso, a Hispanic-Serving Institution located in the U.S.-Mexico Border region. Findings of a sample of n = 7,633 university students are presented in the first cross-sectional, two-year food and housing security study on campus administered via platform Campus Labs Baseline. The first sample in 2019 consisted of n = 2,615 students representing 10.4% of student enrollment (25,177 total 2019 enrollment), and the second sample in 2020 was n = 5,018 representing 20.2% of student enrollment (24,879 total 2020 enrollment). To measure food security, the six-item short form of the U.S. Department of Agriculture (USDA) Household Food Security Survey Module was used. To document housing security, we created questions informed by student input. In this study, survey results are reported, and tests are conducted to assess the relationships between various student characteristics and food and housing security. Student characteristics significantly impacting food and housing security are probed further using data visualizations and subpopulation analysis with a focus on analyzing factors impacted by the COVID-19 pandemic. Results indicate that employment status, consistent employment status, hours per week, academic level, number of dependents, and gender are all factors associated with food security during the pandemic but not prior to the pandemic. Other factors, including, college affiliation, ethnicity/race, having any dependents and being head of household, living alone, mode of campus transportation and mode of the transportation, household income, and age, all were associated with food security in both academic years. Using these results, a critical analysis of past interventions addressing food and housing security is presented with a focus on changes made during the pandemic. Recommendations are made for further data-driven interventions and future steps.